Key genes and pathways in tumor‐educated dendritic cells by bioinformatical analysis. (10th October 2019) - Ma, Chenglong; Su, MingMing; Shen, Kai; Chen, Jie; Ning, Yongling; Qi, Chunjian
Abstract: Specific tumor microenvironment signaling might prevent the maturation of dendritic cells (DCs) with tolerogenic and immunosuppressive potential accounting for antigen‐specific unresponsiveness in the lymphoid organs and in the periphery. In the present study, dendritic cells treated with LLC lung cancer cell or 4T1 breast cancer cell culture supernatants significantly down‐regulated the expression of co‐stimulatory molecules MHC‐II, CD40, CD80, but up‐regulated the inhibitory molecule PD‐L1/L2, VISTA, and increased the messengerRNA levels of interleukin (IL)‐6, arginase I, and IL‐10, but decreased tumor necrosis factor‐α and IL‐12a. RNA was isolated from the dendritic cells with or without tumor supernatant stimulation and RNA sequencing was done. Then the differential expression genes were sorted, the candidate genes were analyzed and pathway enrichment analysis was done, and the associated protein–protein interaction network (PPI) was established. After integrated bioinformatical analysis, 405 (279 up‐regulated and 126 down‐regulated) consistently differential expression genes were identified. Using gene ontology and pathway analysis, it was found that differential expression genes were mainly enriched in the immune response, cell–cell interaction, hemostasis, and cell surface interactions with the vascular wall. The PPI data demonstrated that 236 nodes were classified with 1072 edges, and the most remarkable three modules involved 53 central node genes associated with cell survival, cell‐substrate adhesion, chemotaxis, migration, immune response, and complement receptor mediated signaling pathway. These findings revealed the immune status of dendritic cells in the tumor environment.